Ultrahigh Resolution Pixelated Top‐Emitting Quantum‐Dot Light‐Emitting Diodes Enabled by Color‐Converting Cavities (Small Methods 1/2022). Issue 1 (18th January 2022) - Chen, Lianna; Qin, Zhiyuan; Chen, Shuming
Abstract : Inside Front Cover In article number 2101090, Chen and co‐workers have developed the photopatternable color‐converting cavity to realize ultrahigh resolution pixelated red, green, and blue quantum‐dot (QD) LED arrays. By simply photopatterning the indium‐zinc‐oxide phase tuning layers, the cavity can selectively convert the unpatterned QD white emission as color‐saturated and color‐stable red, green, and blue emission with a resolution of ≈1700 pixel‐per‐inch and a color gamut of 111% NTSC. The demonstrated architecture could find potential applications in various displays ranging from cell phone to emerging virtual reality and augmented reality displays.